Measuring the value relevance of financial information for strategic decision-making and performance of Nigerian listed firms - Henry Osahon Osazevbaru (Trends Economics and Management, 2020)
Purpose of the article: Management has traditionally used financial information for strategic decision-making. This study investigates the value relevance of financial information contained in earnings per share and operating cash flow per share for strategic decision-making and hence performance. It utilized secondary data extracted from annual reports and accounts of fortythree (43) listed firms on the Nigerian Stock Exchange over the period of 2006-2017. Methodology/methods: The collected data were subjected to analysis using the non-linear symmetric Generalized Autoregressive Conditional Heteroscedasticity (GARCH (1 1)) model, which is capable of handling time varying properties of financial time series to measure the statistical significance of the association between the variables of interest. Scientific aim: The paper is aimed at empirically investigating the value relevance of financial information to ascertain its potency for handling strategic decisions of listed firms in Nigeria. This is to digress from the contextual factors in the decision-making process and construct an integrated link between value relevance research and strategic management. Findings: The study found that earnings per share and operating cash flow per share are individually and jointly value relevant in strategic decisions and performance. Conclusion: It is necessary to pay attention to the financial information system of an organization to enhance the quality of services it can provide to strategic management. It is necessary to pursue the fundamental quality of relevance that guarantees predictive, materiality and confirmatory values and enhancing quality that measures usefulness by both management and regulators.
Keywords: M1; M21; L25; 650; conditional variance; information system; persistence function; announcement effect; predictive value